The Impact of E-Service Quality on E-Customer Loyalty through E-Customer Satisfaction as Intervening Variable (Case of LinkAja App in Indonesia) - Hilma Maulida; Mahir Pradana (Universitas Muslim Indonesia, 2022)
In the business service, the main focus lies on the quality of service. Good quality of service can give rise to the highest satisfaction from consumers to create an emotional bond of consumer loyalty to a product. LinkAja (a fintech app in Indonesia) has an interesting phenomenon to be observed, seeing that there are many complaints about failed application login access, features which are difficult to be used, difficulty in upgrading full-service, difficulty in withdrawal features. However, customer service who should be able to help user’s problems is felt to be less helpful; thus, users feel abandoned. The purpose of this study is to analyze the effect of the variable e-service quality, e-customer satisfaction, e-customer loyalty on LinkAja application users in Indonesia. The research uses descriptive with a quantitative approach using purposive sampling, given to 108 respondents. This study uses structural equation modelling (SEM). The data was collected by distributing online questionnaires and then processed using the SmartPLS 3.0 software. The results obtained in this study are: e-service quality has a positive and significant effect on e-customer satisfaction, e-customer satisfaction has a positive and significant effect on e-customer loyalty, and e-service quality has an indirect effect on e-customer loyalty through e-customer satisfaction. For this reason, LinkAja should consider improving the quality of electronic services because it would affect the customer satisfaction and loyalty.